2020
DOI: 10.1186/s12877-020-01830-2
|View full text |Cite
|
Sign up to set email alerts
|

Low calf circumference is associated with frailty in diabetic adults aged over 80 years

Abstract: Background Frailty is now seen as a significant factor in older people with diabetes, whose mortality and disability increased. This study aims to investigate the association between calf circumference (CC) with frailty in diabetic adults aged over 80 years. Methods A cross-sectional analysis was performed on the data of 426 diabetic adults aged over 80 years. On admission, demographic data and laboratory parameters were recorded. CC was measured on the lower right leg at the point of the maximal circumferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
1
4
0
1
Order By: Relevance
“…As observed in other studies 6 , 10 , 30 , 39 , 40 , different rates of malnutrition were verified by comparing the indicators and the nutritional assessment instruments used in the population examined 31 . The NRS was a sensitive tool for diagnosing patients at nutritional risk (48.4%); by clustering the malnourished patients with those at risk of malnutrition, according to the MNA, the total rate was 64.5%.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…As observed in other studies 6 , 10 , 30 , 39 , 40 , different rates of malnutrition were verified by comparing the indicators and the nutritional assessment instruments used in the population examined 31 . The NRS was a sensitive tool for diagnosing patients at nutritional risk (48.4%); by clustering the malnourished patients with those at risk of malnutrition, according to the MNA, the total rate was 64.5%.…”
Section: Discussionsupporting
confidence: 71%
“…Our study found no association between CC and diseases. Other papers have pointed to CC as an easy measure capable of predicting falls in older adult patients on hemodialysis 27 , and as a valuable tool for predicting the risk of sarcopenia in OiP with hip fractures 4 ; also associated low CC values with frailty in diabetics older adult aged over 80 years 40 , and that CC showed good accuracy, sensitivity, and specificity for detecting malnutrition in both genders 3 . Another recent study that investigated the relationship between CC and AMC demonstrated that CC was associated with the risk of pneumonia 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the radiological modalities for assessing muscle mass are convincing in terms of accuracy compared with CC determination, CC measurement in the elderly additionally impresses with its valuable predictability of fall events, frailty, malnutrition, morbidity and mortality [ 16 , 21 25 ] . The anthropometric method for recording CC provides a viable and cost-effective option for diagnosing “confirmed sarcopenia” in the elderly according to the diagnostic algorithm of the EWGSOP-2 guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we suggested that decreasing CC and increasing FPG were all independent risk factors for nutritional risk. Our previous study identified that CC is strongly related to frailty in diabetic adults aged over 80 years [ 23 ]. As geriatrics are shifting towards identifying early stages of disability, understanding frailty and sarcopenia is essential and is still developing in the quest to prevent physical dependence.…”
Section: Discussionmentioning
confidence: 99%